2023
DOI: 10.1186/s12885-023-10821-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting acute radiation dermatitis in breast cancer: a prospective cohort study

Abstract: Background Acute radiation dermatitis (ARD) is one of the most common acute adverse reactions in breast cancer patients during and immediately after radiotherapy. As ARD affects patient quality of life, it is important to conduct individualized risk assessments of patients in order to identify those patients most at risk of developing severe ARD. Methods The data of breast cancer patients who received radiotherapy were prospectively collected and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…ARD is the most common toxicity occurring during the course of RT or shortly afterwards (5). In previous studies, the prevalence of grade ≥2 ARD ranged between 3% and 76% (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Considering this wide range, additional studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…ARD is the most common toxicity occurring during the course of RT or shortly afterwards (5). In previous studies, the prevalence of grade ≥2 ARD ranged between 3% and 76% (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Considering this wide range, additional studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Normo-fractionated radiotherapy was associated with a higher risk of acute dermatitis in several studies and review articles (4, 5, 13, 15-17, 21-23, 31-33). So were the administration of a radiation boost (4,5,19,32,34) and the history of smoking prior to or during the course of radiotherapy (4,12,16,29,35,36). Diabetes mellitus was associated with an increased risk of acute dermatitis in one prospective cohort study and a meta-analysis (4,29).…”
Section: Discussionmentioning
confidence: 99%
“…So were the administration of a radiation boost (4,5,19,32,34) and the history of smoking prior to or during the course of radiotherapy (4,12,16,29,35,36). Diabetes mellitus was associated with an increased risk of acute dermatitis in one prospective cohort study and a meta-analysis (4,29). In addition, a prospective trial showed a trend for an association between diabetes mellitus and radiation dermatitis (37), and another study found an association between diabetes mellitus and late radiationrelated skin toxicity (19).…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is widely used in the clinical treatment of cancer, more than 50% of cancer patients need radiotherapy [ 3] ,it is called three traditional cancer therapies together with surgery and chemotherapy. However, when radiation kills tumor cells, it also causes an acute reaction in the irradiated area of normal skin [ 4] .95% of cancer patients receive radiotherapy will appear acute radioactive dermatitis (Acute Radiation Dermatitis, ARD) [ 5] .…”
Section: Introductionmentioning
confidence: 99%